Radiogenic helium concentration and isotope variations in crustal gas pools from Sichuan Basin, China. (June 2020) - Wang, Xiaofeng; Liu, Wenhui; Li, Xiaobin; Liu, Quanyou; Tao, Cheng; Xu, Yongchang
Abstract: Helium is an exhaustible natural resource and the main commercial helium was separated from helium-rich natural gas. The helium in the sedimentary basin is mainly the radiogenic origin of crustal rocks with high level of uranium and thorium. Data from 242 natural gas samples were used to investigate the distribution and formation mechanism of helium-rich gases in the Sichuan Basin of China. All gas samples show remarkably low 3 He/ 4 He ratios with ranging from 0.002 to 0.05 Ra, which represent typical crustal helium. The Weiyuan gas pool in the southern Sichuan Basin possesses high levels of helium (1500–18770 ppm, average 2785.7 ppm) in Precambrian and Cambrian strata. A positive relationship were observed in the helium and nitrogen contents increased with reservoir layer age for all Weiyuan gas samples. Presinian granite was considered as the main helium source for the Weiyuan gas pool. Gaoshiti–Moxi and Weiyuan gas pools belonged to the same ancient gas pool before the Late Cretaceous, but the helium abundance of Gaoshiti–Moxi gas pool is relatively low (200–891 ppm). The change of pressure and fracture system caused by the uplift of Weiyuan structure in the Himalayan orogenesis led to the helium accumulation and enrichment of Weiyuan gas pool. The shale of the Silurian Longmaxi Formation has high contents of uranium and thorium and generated a large amount of helium while forming large quantities of hydrocarbon gases. Generally, the helium abundance of shale gases and conventional gases generated from the Longmaxi Formation ranges from 63 to 1500 ppm and some of the gas pool are sufficient for commercial helium resource exploitation. Therefore, the relative quantities of helium and hydrocarbon gases are act as a key factor influencing the formation of helium-rich natural gas reservoirs. Highlights: Helium in the sedimentary basin is mainly the radiogenic origin. Helium-rich gas is generally the crust-derived heterogenous type. Presinian granite was the main source of helium in the Weiyuan gas field.